Creep-fatigue crack growth behaviour of P91 steels - Norhaida, Ab. Razak; Davies, C. M.; Nikbin, K. M. (Elsevier B.V., 2016)
The importance of predicting failure due to combined creep-fatigue crack growth in high temperature power-plant components has become of great importance importance due to the need for plant to ‘load follow’ in response to fluctuations in demands and the availability of renewables. P91 steel has been widely utilized in conventional plant components. Creep fatigue crack growth (CFCG) tests have been performed on compact specimens at temperatures ranging between 600° C to 625° C. The experimental results have been compared to static creep, high cycle fatigue and CFCG test data available in literature on P91 steel. The CFCG data has been characterised using stress intensity factor range parameter, ΔK and C* parameter. The crack growth per cycle and ∆K relationship shows that at high frequency, the CFCG behaviour tends to that of high cycle fatigue crack growth and at low frequency, the contribution of creep becomes increasingly more significant. The correlation between crack growth rate and C* parameter, shows that most CFCG data fall within the creep crack growth (CCG) P91 data band which may indicate that the crack growth behaviour is dominated by creep processes. Fractography has also shown an intergranular, ductile fracture surface indicating creep dominance for the conditions considered. A linear cummulative rule has ben used to predict the CFCG experimental result.